STUDI TAFSIR AL-MARAGHI KARYA AHMAD MUSTHAFA AL-MARAGHI - Supriadi Supriadi (Jurnal Asy-Syukriyyah, 2016)
Writing tafsir al-Maraghi is inseparable from the sense of responsibility and scientific demands of a writer as a scholar commentary, in addressing the problems of contemporary society that need solving quickly and accurately. He felt called to offer solutions based on the meaning contained in the passage of the Koran. For that reason tafsir al-Maraghi appear in a modern style, the interpretation adapted to the conditions of society that has been developed. Al-Maraghi successfully combining of several methods of interpretation that exist, through the book of his commentary, al-Maraghi also developed a new interpretation of one of the elements, ie, split between global explanation (ijmali) and an explanation of the details (tahlili). Thought Al Maraghi also not free from the influence of two great scholars of Al-Azhar, Sheikh Muhammad Abduh and Sheikh Muhammad Rashid